Bribery Crimes in Two Paradigms: A Comparative Study Betwewn Criminal Law and Islamic Criminal Law - Nurhaliza; Ramadani (Universitas Muhammadiyah Surabaya, 2025)
Bribery is a form of abuse of power that not only undermines justice but also erodes the integrity of the legal system. This study aims to evaluate the level of public understanding of bribery practices, analyze its regulation in national criminal law and Islamic criminal law, and examine the role of law enforcement in prevention efforts. The research method used is empirical legal research, combining normative analysis of legislation with field data obtained through observation and interviews. The results show that the public's low understanding of the prohibition of bribery and the weakening of the moral integrity of officials and public servants are the main factors driving bribery practices. In positive criminal law, provisions regarding bribery are regulated in Law Number 31 of 1999 concerning Eradication of Corruption Crimes, while in Islamic criminal law, bribery is considered a jarimah ta'zir because it damages the public interest (maslahah 'ammah). Sanctions against perpetrators are determined based on the judge's discretion, taking into account the degree of guilt and its impact on society. This study emphasizes the need for a more comprehensive preventive and repressive approach in both legal systems to strengthen the effectiveness of combating bribery and foster a culture of integrity in law.